A review of software products for implementing didactic reduction: EXCEL, STATISTICA, AND SPSS - Shmatkov, D. (Problems of Engineer-Pedagogical Education, 2020)
In the article, a review of statistical software products such as Excel, STATISTICA, and SPSS is provided in the context of implementation of a didactic reduction method which was developed and proved to be effective. Taking into account the developed criteria, the effectiveness of using software products at the following stages was substantiated: formation of the initial set of research objects and particular indicators that characterize certain aspects of the development of these objects; calculation of an integral indicator to obtain a generalized assessment of the level of development of the research objects; identification of the influence of each particular indicator on changes in the integral indicator and reduction of indicators that have the least impact; clustering of the research objects and reduction of part of the objects based on the averaged characteristics of the groups. The system of criteria for evaluating software products consisted of the following: prevalence and availability; flexibility and functionality (the ability to enter formulas manually; the ability to set / change a type and parameters of illustrations; the ability to implement the method using a single tool); interface (the presence of cascading windows; the ability to receive results in a separate file / window; presentation of available functions in a hierarchical form); speed of analysis (the need for additional steps for analysis; clarity, consistency and visibility of results presentation; overall performance, taking into account the time spent on analysis); the presence of additional special functions. A detailed example of the implementation of the didactic reduction method in the process of studying the subject area of the development of social media and big data is presented. As a result of combining Excel, STATISTICA and SPSS, using the three most suitable combinations, it was defined that combining Excel and STATISTICA is the most effective way for the method implementation. In this case, Excel is proposed to be used at the first and second stages, and STATISTICA – at the third and fourth stages.